Traditional Chinese Medicine for Topical Treatment of Skeletal Muscle Injury - Wing-Sum Siu; Hui Ma; Wen Cheng; Wai-Ting Shum; Ping-Chung Leung (MDPI AG, 2023)
Muscle injuries are common musculoskeletal problems, but the pharmaceutical agent for muscle repair and healing is insufficient. Traditional Chinese Medicine (TCM) frequently uses topical treatments to treat muscle injuries, although scientific evidence supporting their efficacy is scarce. In this study, an in vitro assay was used to test the cytotoxicity of a topical TCM formula containing Carthami Flos, Dipsaci Radix, and Rhei Rhizoma (CDR). Then, a muscle contusion rat model was developed to investigate the in vivo effect and basic mechanisms underlying CDR on muscle regeneration. The in vitro assay illustrated that CDR was non-cytotoxic to immortalized rat myoblast culture and increased cell viability. Histological results demonstrated that the CDR treatment facilitated muscle repair by increasing the number of new muscle fibers and promoting muscle integrity. The CDR treatment also upregulated the expression of Pax7, MyoD and myogenin, as evidenced by an immunohistochemical study. A gene expression analysis indicated that the CDR treatment accelerated the regeneration and remodeling phases during muscle repair. This study demonstrated that topical CDR treatment was effective at facilitating muscle injury repair.